Central versus Peripheral CTEPH-Clinical and Hemodynamic Specifications - Kaldararova, Monika; Simkova, Iveta; Bohacekova, Marcela; Reptova, Adriana; Hlavata, Tereza; Pacak, Jozef; Lindner, Jaroslav; Jansa, Pavel (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: Chronic thromboembolic pulmonary hypertension (CTEPH) is a chronic progressive disease, resulting from persistent arterial obstruction combined with small-vessel remodeling. Central and peripheral CTEPH are distinguished, according to the dominant lesion's location. This is important for surgical or percutaneous interventional assessment or for medical treatment. Material and Methods: Eighty-one patients (51 male/30 female) with confirmed CTEPH were analyzed, while the CENTRAL type included 51 patients (63%) and the PERIPHERAL type 30 patients (37%). Results: A significant difference in CENTRAL type vs. PERIPHERAL type was determined in gender (male 72.5% vs. 46.7%; p = 0.0198). No difference was found in age, functional status, or echocardiographic parameters. Invasive hemodynamic parameters showed a significant difference in mean pulmonary arterial pressure (46 vs. 58 mmHg; p = 0.0002), transpulmonary gradient (34 vs. 47 mmHg; p = 0.0005), and cardiac index (2.04 vs. 2.5 L.min.m2; p = 0.02) but not in pulmonary vascular resistance. Risk factors showed a significant difference only in acute pulmonary embolism (93.8% vs. 60%; p = 0.0002) and malignancy (2% vs. 13.3%; p = 0.0426). Conclusions: Our study showed hemodynamic differences between CENTRAL type vs. PERIPHERAL type CTEPH with a worse hemodynamic picture in CENTRAL form. This may indicate a different pathophysiological response and/or possible additional influences contributing especially to the peripheral pulmonary bed affection.
Keywords: Pulmonary Embolism; risk factors; hemodynamic evaluation; chronic thromboembolic pulmonary hypertension (CTEPH); Chronic Disease; central CTEPH; plicní embolie; chronická nemoc; Hypertension, Pulmonary; mužské pohlaví; cévní rezistence; plicní hypertenze; ženské pohlaví; plíce; Humans; Hemodynamics; hemodynamika; peripheral CTEPH; Vascular Resistance; Female; Lung; lidé; Male